Pengaruh Pendidikan dan Upah Minimum terhadap Ketimpangan Pendapatan Antar Provinsi di Indonesia: Pendekatan Data Panel GMM - Mauludin, Muhamad; Sahrul, Muhamad; Ihsanudin, 3Muhamad Husen (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This study aims to analyze the effect of education and minimum wage on income inequality between provinces in Indonesia during the period 2020–2024. Income inequality is measured using the Williamson Index, with secondary panel data covering 34 provinces. The independent variables consist of education, represented by the average length of schooling, and the provincial minimum wage (UMP), expressed in natural logarithms. The analysis method used is the Generalized Method of Moments (GMM) with the First Difference Arellano–Bond approach to address potential endogeneity and autocorrelation in the dynamic panel data model. The results show that the model used is valid and consistent, as evidenced by the Sargan test (p = 0.296) and Arellano–Bond test (AR(2) = 0.342). Empirically, education has a significant effect on income inequality, while the minimum wage has a negative but statistically insignificant effect. These findings confirm that improving the quality of education is a dominant factor in reducing economic disparities between regions in Indonesia, while minimum wage policies have the potential to serve as an instrument to support more equitable income redistribution.